(untitled) (Journal of Informatics Education and Research, 2025)
In this research paper, we delve into the financial performance and efficiencies of the banks involved in the merger, namely Punjab National Bank (PNB), Canara Bank, Union Bank of India, and Indian Bank. The merger was carried out in such a way that four public-sector banks were formed after the amalgamation of ten banks. Punjab National Bank combined with the United Bank and the Oriental Bank of Commerce and the Syndicate Bank combined with the Canara Bank. The Andhra Bank, the Union Bank, and the Corporation Banks are combined. The Indian Bank combined with the Allahabad Bank. The primary focus is to examine the impact of the merger on key financial indicators such as non-performing assets (NPAs), risk management strategies, and liquidity measures. By employing quantitative methods like Data Envelopment Analysis (DEA) and Multilinear Regression Analysis, we aim to gain insights into the efficiency, productivity, and dependencies among the study variables.